Constructing Interlocking Rationales in Top‐driven Strategic Renewal. (6th March 2012) - Canales, J. Ignacio
Abstract : Under top‐driven change, active involvement of middle managers in strategy‐making requires top and middle to find common ground. The paper offers inductive theoretical development of top managers' role as enablers for the strategic contribution of the middle levels. Central to this role is the symbolic reorganization where the middle managers' position is set. Next, middle managers' operational efficiency allows their performance to be shown and increases their reputation. In consequence, the middle level can actively shape the role suggested by top management, which increases their power base. Finally, when these previous interactions escalate into a two‐way process where the middle and top management contribute to each other's efforts, interlocking rationales are achieved.